The Impact of Microearthquakes Induced by Reservoir Water Level Rise on Stability of Rock Slope - Dongliang Li; Xinrong Liu; Xingwang Li; Yongquan Liu (Shock and Vibration, 2016)
In order to study the impact of frequent microearthquakes induced by water level rise on the stability of rock bedded slopes in the Three Gorges Reservoir (TGR) area, Zhaoshuling Landslide (a representative slope) is selected to study. Safety factors based on probability statistics and FLAC3D are used for numerical simulation (under the operating condition that five earthquakes of Intensity IV are applied to slope in succession after water level rises from 145 m to 175 m). Then the slope’s dynamic stability characteristics and failure mechanism are analyzed. The study shows that slope deformation is evidently the result of thrust load. The deformation starts from the steeply dipping segment in the middle part of slip mass and is controlled by the soft interlayer. Shear failure tends to occur along the soft interlayer and the horizontal slip displacement increases from the rear to the front of the slope. The steeply dipping segment shows a general downslide trend. Although the gentle slope platform on the rear edge is relatively stable, it is vulnerable to tensile fractures which are precursors of landslide. Under the same failure probability, as the number of microearthquake occurrences increases, the safety factor of slope under microearthquake action decreases gradually.